The Anti-Saccharomyces Cerevisiae Antibody Assay in a Province-Wide Practice: Accurate in Identifying Cases of Crohn’s Disease and Predicting Inflammatory Disease - Brinderjit Kaila; Kenneth Orr; Charles N Bernstein (Canadian Journal of Gastroenterology)
OBJECTIVE: To determine the utility of the anti-Saccharomyces cerevisiae antibody (ASCA) ELISA test developed in Manitoba in 2001 in a population-wide sample referred from physicians across Manitoba in their investigation of patients with gastrointestinal symptoms.